2020
DOI: 10.1101/2020.09.17.20195867
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Dosing Of Thromboprophylaxis And Mortality In Critically Ill Covid-19 Patients

Abstract: Background: A substantial proportion of critically ill COVID-19 patients develop thromboembolic complications, but it is unclear whether higher doses of thromboprophylaxis are associated with lower mortality rates. The purpose of the study was to evaluate the association of initial dosing strategy of thromboprophylaxis in critically ill COVID-19 patients and the risk of death, thromboembolism, and bleeding. Method: All critically ill COVID-19 patients admitted to two intensive care units in March and April 202… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
49
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(51 citation statements)
references
References 27 publications
2
49
0
Order By: Relevance
“…The incidence of cardiac dysfunction was in line with other studies of patients hospitalized, whose COVID-19 disease severities ranged from mild to severe, and where LV dysfunction was found in 10 to 42% and RV dysfunction in 14 to 39% [15,23,24]. One reason for the relatively low incidence of RV dysfunction may have been the liberal use of thromboprophylaxis that was introduced early in the study period [25], leading to less pulmonary embolism than in many earlier studies [15,26]. We did not assess patients with tissue doppler or strain analysis, modalities that are more sensitive for the detection of ventricular dysfunction, which could explain a comparative low incidence of cardiac dysfunction in our study.…”
Section: Discussionsupporting
confidence: 86%
“…The incidence of cardiac dysfunction was in line with other studies of patients hospitalized, whose COVID-19 disease severities ranged from mild to severe, and where LV dysfunction was found in 10 to 42% and RV dysfunction in 14 to 39% [15,23,24]. One reason for the relatively low incidence of RV dysfunction may have been the liberal use of thromboprophylaxis that was introduced early in the study period [25], leading to less pulmonary embolism than in many earlier studies [15,26]. We did not assess patients with tissue doppler or strain analysis, modalities that are more sensitive for the detection of ventricular dysfunction, which could explain a comparative low incidence of cardiac dysfunction in our study.…”
Section: Discussionsupporting
confidence: 86%
“…Importantly, there was no difference in the development of bleeding events among the three groups. 27 Similar findings were identified in a retrospective study from Abu Dhabi albeit finding that therapeutic anticoagulation, rather than enhanced chemoprophylaxis, was associated with major bleeding. 28 Another retrospective observational study of 468 hospitalized patients in the United States found that initial use of enhanced dosing thromboprophylaxis correlated with a downtrend in D-dimer levels and was associated with improved 30-day mortality without a significant increased rate of bleeding.…”
Section: What Type Of Venous Thromboembolism (Vte) Prophylaxissupporting
confidence: 76%
“…Jonmarker et al compared the outcomes of COVID-19 ICU patients treated with standard, intermediate, and full dose anti-coagulation. 100 They found that mortality was lower in high dose (13.5%) vs medium dose (25.0%) and low dose thromboprophylaxis (38.8%) groups, p ¼ 0.02.…”
Section: Anticoagulation and Covid-19mentioning
confidence: 93%